2011
DOI: 10.3138/ptc.2010-18
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Electrophysiological, and Metabolic Characteristics of Skeletal Muscle in People with End-Stage Renal Disease: A Critical Review

Abstract: Purpose: Fatigue is one of the most frequent debilitating symptoms reported by people with end-stage renal disease (ESRD) on haemodialysis (HD) therapy. A wide range of underlying abnormalities, including skeletal muscle weakness, have been implicated as causes of this fatigue. Skeletal muscle weakness is well established in this population, and such muscle weakness is amenable to physical therapy treatment. The purpose of this review was to identify morphological, electrophysiological, and metabolic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…Together these and our results [in a larger species and a muscle expressing >95% IIX(IId) myosin, (Aigner et al, 1993;Hämäläinen and Pette, 1993)] could indicate a muscle type specificity of fiber atrophy in the early stages of CRI. Our findings are consistent with human studies reporting muscle atrophy in advanced kidney patients (Johansen et al, 2003;Sakkas et al, 2003a;Sawant et al, 2011) and suggest that atrophy could appreciably affect fast muscles which are normally tasked to provide high levels of muscle power, earlier during the disease progress.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Together these and our results [in a larger species and a muscle expressing >95% IIX(IId) myosin, (Aigner et al, 1993;Hämäläinen and Pette, 1993)] could indicate a muscle type specificity of fiber atrophy in the early stages of CRI. Our findings are consistent with human studies reporting muscle atrophy in advanced kidney patients (Johansen et al, 2003;Sakkas et al, 2003a;Sawant et al, 2011) and suggest that atrophy could appreciably affect fast muscles which are normally tasked to provide high levels of muscle power, earlier during the disease progress.…”
Section: Discussionsupporting
confidence: 92%
“…We observed significantly smaller CSAs in UREM psoas fibers compared to CON (by ~11%) in agreement to human studies. In end-stage disease, muscle atrophy is ~ 27% (Sakkas et al, 2003b) affecting mostly the fast type IIA and IIX muscle fibers (Sakkas et al, 2003a;Sawant et al, 2011). Recently Acevedo et al, (Acevedo et al, 2015) reported no evident atrophy in the tibialis cranialis (a mixed fast hindlimb muscle) of surgically-induced uremic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevant parameters (voltage, pH, and fractional volume) for estimating the unbound partitioning within muscle (Guderley et al, 2006;Sawant et al, 2011), liver (Peters, 1984;Saito et al, 1992;Plettenberg et al, 2008), and the pancreas (Nishiyama and Petersen, 1974;Morgan et al, 1986;Taga et al, 1993) are provided in Table 1. The key approximation that will be made within this framework is that the transmembrane permeation is similar across various cell and organelle types and that fu is a whole tissue parameter.…”
Section: Methodsmentioning
confidence: 99%
“…An array of changes in the morphological, electrophysiological and metabolic characteristics of skeletal muscle structure in patients with HD lead to muscle weakness. These changes include myopathic, neuropathic, and mixed changes existing independently . Additionally, atrophy of type II fibers was observed in the patients with HD in several studies .…”
Section: Discussionmentioning
confidence: 98%